2002
DOI: 10.1177/1049732302238245
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to Understand: The Experience of Nonsmoking Parents with Adolescents who Smoke

Abstract: Smoking among adolescents is a major public health concern. Most parents would not want their children engaged in this risk-taking behavior. Although a majority of parents of smokers are themselves smokers, many are nonsmokers. The purpose of this grounded theory study was to understand what nonsmoking parents experience due to their adolescent children 's smoking behavior. The purposive sample consisted of 25 parents. The interview data generated the theory that nonsmoking parents struggle to understand their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several authors indicated that they used theoretical sampling by modifying data collection procedures⎯ most often interview questions⎯as their study progressed. Theoretical sampling was said to occur when: (a) interview questions were refocused to gain specific information regarding an emerging concept (Borrayo, Buki, & Feigal, 2005;de la Cuesta, 2005;Sandgren, Thulesius, Fridlund, & Petersson, 2006;Small, Brennan-Hunter, Best, & Solberg, 2002), (b) interviews were redirected as some categories became saturated and participants introduced new concepts (Milliken & Northcott, 2003), and (c) interviews were modified to test working hypotheses (McNeill, 2004) or validate theoretical concepts (Milliken & Northcott, 2003). Authors often did not detail how emerging concepts necessitated a change in interview strategies or how the interview questions were actually modified according the stage of analysis.…”
Section: Theoretical Sampling In Published Grounded Theory Studiesmentioning
confidence: 99%
“…Several authors indicated that they used theoretical sampling by modifying data collection procedures⎯ most often interview questions⎯as their study progressed. Theoretical sampling was said to occur when: (a) interview questions were refocused to gain specific information regarding an emerging concept (Borrayo, Buki, & Feigal, 2005;de la Cuesta, 2005;Sandgren, Thulesius, Fridlund, & Petersson, 2006;Small, Brennan-Hunter, Best, & Solberg, 2002), (b) interviews were redirected as some categories became saturated and participants introduced new concepts (Milliken & Northcott, 2003), and (c) interviews were modified to test working hypotheses (McNeill, 2004) or validate theoretical concepts (Milliken & Northcott, 2003). Authors often did not detail how emerging concepts necessitated a change in interview strategies or how the interview questions were actually modified according the stage of analysis.…”
Section: Theoretical Sampling In Published Grounded Theory Studiesmentioning
confidence: 99%
“…Interactions related to tobacco use were the focus of the four remaining studies and included studies examining nonsmoking parents' interactions with smoking adolescents (Small, Brennan-Hunter, Best, & Solberg, 2002), couple interactions related to tobacco use Bottorff, Oliffe, et al, 2006b), and interaction dynamics during telephone support for smoking cessation (Bottorff et al, 2004a). With one exception (Bottorff et al, 2004a), the primary data collection method was interviews with samples that ranged from 17 to 35 participants.…”
Section: Grounded Theorymentioning
confidence: 99%